Analisis Pengaruh Variabel Moneter Terhadap Perkembangan Ekonomi Negara ASEAN - Mutia Yollanda; Fitri Rahmah Ul Hasanah (UIN Imam Bonjol Padang, 2023)
This study aims to determine the effect of inflation and exchange rates on ASEAN countries' gross domestic product (GDP). The data used is secondary data accessed through the world bank from 2019 to 2021, which consists of 30 data. The independent variables used in this data are exchange rates and inflation, while the dependent variable used is gross domestic product (GDP). The panel data regression used in this study includes the common effect model, the fixed effect model and the random effect model. Based on the Chow and Hausman tests conducted, the best model in this study was the random effect model (REM). The best equation in this research is given by the equation . his study uses robustness because the normality test on the classical assumption is not fulfilled. Based on the test results, the USD exchange rate and inflation variables have a significant effect on the GDP variable. While the inflation variable has no significant effect on the GDP variable.